Implementation of a Polysilicon Micro Electro-Thermal Detector in Gas Chromatography System with Applications in Portable Environmental Monitoring. (1st January 2015) - Mahdavifar, Alireza; Navaei, Milad; Hesketh, Peter J.; Dimandja, John D.; Stetter, Joseph R.; McMurray, Gary
Abstract : Thermal conductivity detectors work based on electro-thermal interaction between rate of heat loss to the surrounding gas from a hot element and resistance change due to temperature variation of the heater. Our developed ultra-low power polysilicon microbridge TCD provides ultra-fast response time and high sensitivity along with lower power consumption that makes it suitable for portable GC in environmental and bioengineering applications. In this work we modeled and tested the microTCD operation as a detector in a GC system. MicroTCD was packaged and connected to a 3 m long separation column in GC and was tested with injections of hexane and mixture of six standard compounds in helium carrier. Modeling and experimental results show that the effect of carrier gas flow speed on power consumption and heat loss from the microbridge is small and therefore the microTCD is insensitive to various typical flow rates. A new method of excitation and measurement of the detector was utilized to avoid base temperature drifting and achieve superior resolution in extended range of operations while consuming only 0.4 mW power. The microTCD response for different compound was obtained and compared with standard Flame Ionization Detector (FID) results.